Вы находитесь на странице: 1из 3

2009 4.

(a) A light inextensible string passes over a small fixed smooth pulley. A particle A of mass 10 kg is attached to one end of the string and a particle B of mass 5 kg is attached to the other end. The system is released from rest when B touches the ground and A is 1 m above the ground. Find (i) the speed of A as it hits the ground (ii) the height that B rises above the horizontal ground. SOLUTION (i)
1m

FNet = ma W1 T = 10a 10 g T = 10a...(1)


a T T a

FNet = ma T W2 = 5a T 5 g = 5a...(2)

10 kg A

1m

W1 B 5 kg

10 g T = 10a...(1) T 5 g = 5a.......(2) 5g = 15a a = g m s


1 3 2

W2 (ii) Particle B:

u=

2 a=1 3 g m s

2g m s 1 3 v = 0 m s 1 a = g m s 2 s=?

v 2 = u 2 + 2as 2g 0 = + 2( g ) s 3 2g s=1 2 gs = 3 m 3
2 4 3 2

u = 0 m s 1 s =1 m v=?

v 2 = u 2 + 2as
2 v 2 = 02 + 2( 1 3 g )(1) = 3 g

v =

2g m s 1 3

Total distance: 1 m + 1 3 m =

Kieran Mills & Tony Kelly (www.studentxpress.ie)

(b) A mass m1 kg is at rest on a smooth horizontal table. It is attached to a m1 light inextensible string. The string, after passing over a small fixed pulley at the edge of the table, passes under a small moveable pulley C, of mass m2 kg. The string then passes over a smooth fixed pulley and supports a mass of 1 kg. The system is released from rest. (i) Find, in terms of m1 and m2, the tension in the string. (ii) The pulley C will remain at rest if 2 1 = k . m2 m1 . Find the value of k. SOLUTION (i)
m1 T
1 2 (a

C 1 kg

+ b)

T W1 m2 C

T T b

FNet = ma m1 particle: y direction: R W1 = m1 (0) R = W1 x direction: T = m1a....(1)


W3 W2 1 kg

m2 pulley: W2 2T = m [ (a + b)]
1 2 2

T = m1a....(1) a = T g = b....(3)

T m1

m2 g 2T = 1 2 m2 ( a + b)....( 2) 1 kg particle: T W3 = b T g = b....(3)

m2 g 2T = 1 2 m2 ( a + b)....( 2)

T m2 g 2T = 1 +T g 2 m2 m1 2m1m2 g 4m1T = m2T + m1m2T m1m2 g 3m1m2 g = (4m1 + m2 + m1m2 )T T = 3m1m2 g 4m1 + m2 + m1m2

Kieran Mills & Tony Kelly (www.studentxpress.ie)

(ii) If the pulley is to remain at rest, its acceleration is equal to zero. m2 g 2T = 1 2 m2 ( a + b)...( 2) 1 2 ( a + b) = g g= 2T =0 m2

6m1 g 4m1 + m2 + m1m2

4m1 + m2 + m1m2 = 6m1 m1m2 = 2m1 m2 1= 2 1 m2 m1

k = 1

Kieran Mills & Tony Kelly (www.studentxpress.ie)